Hypertension Profile of Angiotensin Receptor Blocker From Matoa Leaves Extract (Pometia Pinnata J.R. Foster & G. Foster) In Angiotensin II Induced-Male Rat With Blood Volume Parameter - Novi Elisa; Fransiskus Xaverius Sulistiyanto Wibowo Sutardjo; Jaka Seprianto Lepangkari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Hypertension is a problem of cardiovascular disease that occurs in many people. The leaves of matoa, which have another name, Pometia pinnata, are one of the plants used as traditional medicine for the treatment of hypertension. The active compounds of matoa leaves are flavonoids. This study aimed to observe the hypertension profile of the Angiotensin Receptor Blocker class. The test animals used in this study were 45 male Wistar rats. Each group consisted of 5 rats induced by angiotensin II, divided into groups, namely normal control, negative control, positive control, a dose of 75g/kgBW, 150g/kgBW, and 300g/kgBW, and observation were done for 14 days. The hypertension profile observed in this study was the blood volume of rats. The percentage reduction in blood volume of rats given the best matoa leaves extract was 300 mg/kgBW, extract which showed mean difference in negative control group with a significance value of <0.05